Mathematical Modeling and Optimization of the Anomalous Hall Angle in Magnetic Topological Semimetals - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2026)
Magnetic topological semimetals like Co3Sn2S2 exhibit a large anomalous Hall angle (θA), making them promising for magnetic sensors and spin-orbit torque (SOT) devices, but scalable synthesis and real-time control remain challenging. This study aimed to predict and optimize θA in Co3Sn2S2, focusing on scalable thin-film deposition and dynamic modulation for enhanced device applicability. A predictive model (θA = arctan(σxy/σxx)) was validated against experimental data (RMSE = 10.59°), followed by simulations of thin-film deposition (substrate temperature: 200–600°C, deposition rate: 0.1–2.0 Å/s) and dynamic modulation (strain: -2% to 2%, electric field: 0–0.5 V/nm). The model accurately predicted θA for Fe-doped Co3Sn2S2 (25.6° vs. 24.8° experimental) but overestimated TbPdBi (error: 10.8°). Thin-film deposition at 208°C and 0.1 Å/s yielded θA = 7.2° (σxy = 528 Ω⁻¹ cm⁻¹, ρxx = 239 μΩ cm), below experimental benchmarks (24.8°). Dynamic modulation at strain = 1.8% and electric field = 0.50 V/nm achieved θA = 7.6° (σxy = 1155 Ω⁻¹ cm⁻¹, ρxx = 115 μΩ cm), suitable for basic sensors but insufficient for SOT devices (θA > 20°). While the framework captures θA trends, current synthesis and modulation methods yield θA values below device requirements, necessitating improvements. Higher deposition temperatures (500°C–600°C), stronger modulation (strain > 3%, electric field > 1.0 V/nm), and advanced modeling (e.g., DFT-derived Berry curvature) are recommended to achieve θA > 15°, enabling practical AHE applications.